Association of relative telomere length with progression of chronic kidney disease in two cohorts: effect modification by smoking and diabetes - Raschenberger, Julia; Kollerits, Barbara; Ritchie, James; Lane, Beverley; Kalra, Philip A.; Ritz, Eberhard; Kronenberg, Florian (Scientific reports, 2015)
Chronic kidney disease (CKD) is a highly progressive disease. We studied the association between relative telomere length (RTL) and CKD progression and tested whether this association is modified by smoking and diabetes mellitus. RTL was measured by qPCR in two prospective cohort studies, the MMKD-Study (n = 166) and the CRISIS-Study (n = 889) with a median follow-up of 4.5 and 2.8 years, respectively. Progression was defined as doubling of baseline serum creatinine (MMKD-Study) and/or end stage renal disease (both studies). 59 and 105 of the patients from MMKD and CRISIS experienced a progression of CKD. Mean standardized pooled RTL was 0.74 ± 0.29. In the meta-analysis shorter RTL at baseline showed a borderline association with CKD progression (HR = 1.07 [95%CI 1.00-1.15]; p = 0.06). We observed an effect modification of RTL and CKD progression by smoking and diabetes (p-values of interaction p = 0.02 and p = 0.09, respectively). Each 0.1 unit shorter RTL was significantly associated with an increased hazard for CKD progression in active-smokers by 44% (HR = 1.44 [1.16-1.81]; p = 0.001) and in patients with diabetes mellitus by 16% (HR = 1.16 [1.01-1.34]; p = 0.03). Estimates were adjusted for baseline age, sex, proteinuria and GFR. This study in two independent cohorts reinforces that RTL is a marker and potentially a pathogenetic factor for CKD progression.
Gesehen am 10.06.2020